1990
DOI: 10.1007/bf02624456
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous transformation and immortalization of human endothelial cells

Abstract: A new cell line from the human umbilical vein has been established and maintained for more than 5 yr (180 generations; 900 population doublings). This strain, designated ECV304, is characterized by a cobblestone monolayer growth pattern, high proliferative potential without any specific growth factor requirement, and anchorage dependency with contact inhibition. Karyotype analysis of this cell line reveals it to be of human chromosomal constitution with a high trisomic karyotype (mode 80). Ultrastructurally, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
241
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(243 citation statements)
references
References 32 publications
1
241
0
1
Order By: Relevance
“…In order to assess cell viability, an MTT cytotoxicity assay consisting of tetrazolium salt reduced to formazan by mitochondrial enzymes of viable cells was used proportionally to its dehydrogenase activity and defined as a 3-(4.5-dimethylthiazol-2-yl)-2.5-diphenyl-tetrazolium bromide colorimetric assay (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to assess cell viability, an MTT cytotoxicity assay consisting of tetrazolium salt reduced to formazan by mitochondrial enzymes of viable cells was used proportionally to its dehydrogenase activity and defined as a 3-(4.5-dimethylthiazol-2-yl)-2.5-diphenyl-tetrazolium bromide colorimetric assay (11).…”
Section: Methodsmentioning
confidence: 99%
“…ECV304 endothelial cells are obtained from the human umbilical cord vein. This line is characterized by a monolayered growth pattern, high proliferative potential, with no growth factor-specific requirement (11).…”
Section: Introdutionmentioning
confidence: 99%
“…ECV cells (spontaneously transformed human umbilical vein endothelial cells; Takahashi et al, 1990) were maintained in RPMI-1640, 10% FCS, 50 IU ml À1 penicillin, 50 mg ml À1 streptomycin and split twice weekly 1:10. ECV cells display the following endothelial cell markers: factor VIII-related antigen (negative), UEA-I and PHM5 (positive) and ultrastructurally endothelium-speci®c Weibel± Palade bodies (Takahashi et al, 1990). Epithelial cell markers, such as cytokeratin, and two other epithelial cell markers are not found (Takahashi et al, 1990).…”
Section: Cell Culturementioning
confidence: 99%
“…HeLa-H2B is a clone from the cervical carcinoma model cell line (HeLa) stably expressing the histone protein H2B fused to GFP (31). ECV-304 was originally described as an immortalized endothelial cell line (32). However, more recent evidence has suggested that ECV-304 is a derivative of the human bladder carcinoma cell line T24 (33).…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%